1991
DOI: 10.1007/bf00260651
|View full text |Cite
|
Sign up to set email alerts
|

Response to heat shock of gene 1, a Drosophila melanogaster small heat shock gene, is developmentally regulated

Abstract: The expression of gene 1, a member of the small heat shock gene family from the Drosophila melanogaster chromosomal locus 67B was studied. In contrast to the other heat shock genes, the response of gene 1 to stress was modulated during development. In the absence of stress, gene 1 was expressed at the beginning of pupation, and at a very low level in adult males. Expression of gene 1 was substantially increased by heat shock in pupae, but was one to two orders of magnitude lower in adults or in embryos. Under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…The most prominent member of the HSP family, HSP70, is tightly regulated and has many protein isoforms encoded by separate gene loci which have distinct regulatory characteristics allowing them to help cells respond to various types of assaults (Daugaard et al, 2007;Tranter et al, 2011). Early studies on HSPs demonstrated that during heat shock various mRNAs encoding HSP proteins, including HSP70, were subject to APA (Lowe & Moran, 1986;Vazquez, 1991). Despite being overlooked for decades, a number of recent studies have begun to investigate the role of APA in regulating HSP70 expression (Kraynik et al, 2015;Tranter et al, 2011).…”
Section: Alternative Polyadenylation Of Hsp Genesmentioning
confidence: 99%
“…The most prominent member of the HSP family, HSP70, is tightly regulated and has many protein isoforms encoded by separate gene loci which have distinct regulatory characteristics allowing them to help cells respond to various types of assaults (Daugaard et al, 2007;Tranter et al, 2011). Early studies on HSPs demonstrated that during heat shock various mRNAs encoding HSP proteins, including HSP70, were subject to APA (Lowe & Moran, 1986;Vazquez, 1991). Despite being overlooked for decades, a number of recent studies have begun to investigate the role of APA in regulating HSP70 expression (Kraynik et al, 2015;Tranter et al, 2011).…”
Section: Alternative Polyadenylation Of Hsp Genesmentioning
confidence: 99%
“…One family of heat shock proteins, the low molecular weight hsps, are known to be developmentally regulated, at least in part through the action of hormones Vazquez, 1991;Billoud et al, 1993;de Jong et al, 1993). The induction of hsps is uncoupled during development, in contrast to the coordinate induction during heat shock .…”
Section: Clams Collected In September 1994mentioning
confidence: 99%